The impact of social capital on firm value - Michele Nascimento Jucá; Albert Fishlow (Contemporary Economics, 2022)
Social capital and value creation are concepts that have been associated in financial literature for a long time and still remain controversial. Social capital refers to a firm's attributes, such as trust, civic attitudes, and relationship networks that enable greater economic development. It is also related to corporate social responsibility, corresponding to a voluntary interest by firms in social and environmental issues with effects upon others. The last global financial crisis - which began in the United States in 2007 - is an exogenous event that allows a study of the impact of a higher level of corporate credibility. In other words, we may verify whether attributes such as trust - measured by social capital - create value. Thus, this study aims at verifying if there was a positive relationship between social capital and corporate value, during the last global financial crisis. To this end, a difference-in-difference test was applied to a sample of 418 Latin American firms. The results confirm the hypothesis that in a financial crisis, firms with more social capital have their value less affected. This fact points to practical implications both for investors and capital market regulators.
Keywords: G32; E22; N26; G3; 330; social capital; corporate social responsibility; firm value; financial crisis; ESG score